Trends in the detection of aquatic non‐indigenous species across global marine, estuarine and freshwater ecosystems: A 50‐year perspective. Issue 12 (2nd October 2020) - Bailey, Sarah A.; Brown, Lyndsay; Campbell, Marnie L.; Canning‐Clode, João; Carlton, James T.; Castro, Nuno; Chainho, Paula; Chan, Farrah T.; Creed, Joel C.; Curd, Amelia; Darling, John; Fofonoff, Paul; et al.
Abstract: Aim: The introduction of aquatic non‐indigenous species (ANS) has become a major driver for global changes in species biogeography. We examined spatial patterns and temporal trends of ANS detections since 1965 to inform conservation policy and management. Location: Global. Methods: We assembled an extensive dataset of first records of detection of ANS (1965–2015) across 49 aquatic ecosystems, including the (a) year of first collection, (b) population status and (c) potential pathway(s) of introduction. Data were analysed at global and regional levels to assess patterns of detection rate, richness and transport pathways. Results: An annual mean of 43 (±16 SD ) primary detections of ANS occurred—one new detection every 8.4 days for 50 years. The global rate of detections was relatively stable during 1965–1995, but increased rapidly after this time, peaking at roughly 66 primary detections per year during 2005–2010 and then declining marginally. Detection rates were variable within and across regions through time. Arthropods, molluscs and fishes were the most frequently reported ANS. Most ANS were likely introduced as stowaways in ships' ballast water or biofouling, although direct evidence is typically absent. Main conclusions: This synthesis highlights the magnitude of recent ANS detections, yet almost certainly represents an underestimate as many ANS go unreported due to limited search effort and diminishing taxonomic expertise. Temporal rates of detection are also confounded by reporting lags, likely contributing to the lower detection rate observed in recent years. There is a critical need to implement standardized, repeated methods across regions and taxa to improve the quality of global‐scale comparisons and sustain core measures over longer time‐scales. It will be fundamental to fill in knowledge gaps given that invasion data representing broad regions of the world's oceans are not yet readily available and to maintain knowledge pipelines for adaptive management.